Patterns of Choosing the Right Sharia Investment for Beginners Amid Global Economic Uncertainty - Husin, Amir; Putri Khairani, Zenni; Matondang, Riswandi; Rahmat, Paisal (El-kahfi | Jurnal Ekonomi Islam, 2025)
This research discusses various types of Islamic investment instruments, such as Islamic stocks, sukuk, Islamic mutual funds, and gold, as well as the criteria for choosing investments that are in accordance with sharia values. Islamic investments are increasingly in demand as an investment alternative that is not only financially beneficial, but also in accordance with Islamic principles. The purpose of this research is to find the right type of Islamic investment for beginners amidst global economic uncertainty. The research also emphasizes how important it is to ensure that every investment instrument has integrity and transparency. The method used for the literature study is a descriptive qualitative approach that analyzes various relevant academic sources through content analysis. The results show that investments with low risk, affordable capital, and in accordance with sharia principles, sharia mutual funds, gold and sharia deposits are the most suitable instruments for beginners amid global economic uncertainty. Factors such as risk profile, financial goals and investment time horizon are also explained as important considerations when making decisions for Islamic mutual funds, sukuk and gold. Investors can choose Islamic investment instruments that are profitable and foster confidence with a good understanding. The results of this study are expected to be an initial guide for novice investors in choosing Islamic investments amidst economic uncertainty.